Hyperoside ameliorates NAFLD in rats via remodeling gut microbiota and reprogramming serum metabolic networks - Huang, Mingchun; Wang, Ya; Li, Yanyan; Zeng, Weiwei (Frontiers in Nutrition, 2026)
ObjectiveThis study explores hyperoside’s therapeutic efficacy in non-alcoholic fatty liver disease (NAFLD) rats and its gut–liver axis mechanisms through integrated gut microbiota and metabolomics analyses.MethodsThe SD rats were divided into five groups (normal control, NAFLD model, low-dose hyperoside [0.6 mg/kg/day], high-dose hyperoside [1.5 mg/kg/day], and rosiglitazone positive control [5 mg/kg/day]) and treated for 12 weeks. Body weight, serum biochemistry (ALT, AST, TC, TG), liver histopathology (H&E, Sirius Red), hepatic mRNA expression (Tlr4, Tnf-α, and α-SMA), gut microbiota (16S rRNA sequencing), and serum metabolites (untargeted metabolomics) were assessed.ResultsHyperoside dose-dependently reduced high-fat, high-sugar diet-induced body weight gain, liver index, and hepatic steatosis/fibrosis, lowered serum liver enzymes and lipid levels, and downregulated pro-inflammatory/fibrotic genes. It remodeled gut microbiota by enriching Lactobacillus and suppressing pathobionts (e.g., Streptococcus, Escherichia-Shigella), reversed metabolic disturbances (e.g., 3-hydroxybutyric acid, diacylglycerols), and targeted glycine/serine/threonine and alpha-linolenic acid metabolism. Beneficial bacteria were negatively correlated with pro-inflammatory metabolites like lysophosphatidylcholine.ConclusionHyperoside ameliorates NAFLD, which is associated with gut microbiota remodeling and modulation of host metabolic networks, supporting its potential as a multi-target therapeutic agent for NAFLD.